A insustentabilidade do desenvolvimento urbano sustentável - Renato Nunes Balbim (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The present Discussion Paper aims to reveal the conception of the idea of sustainable urban development, and how this term can serve geopolitical interests related to maintaining the uneven and combined development discourse on a global and national scale. To this purpose, an etymological and historical rescue of the use of the term was carried out in the main international agreements and conferences which resulted from the environmental and urban development agendas. This allowed an understanding of the political contexts of emergence and dissemination of the term. Just as the discourse of "sustainable development" can be criticized based on contradictions with the development practices, the term sustainable urban development involves profound contradictions since its emergence in the 1990s, gaining strength in the context of the city as a global player, basis of urban services and business stimulated after Habitat III and its New Urban Agenda (NUA). The in-depth look brings to the surface an adjective discourse, generally empty in conceptual and practical substance, which does not seem to contribute to the Sustainable Development Goals' effective fulfillment or even to guarantee the right to a sustainable city, as advocated by the Brazilian City Statute law. It is urgent that the academy, the technical field and society critically appropriate the concepts propagated by international agencies and seek to give effectiveness to the right to a sustainable city.
Keywords: Q01; 330; sustainability; sustainable development; sustainable urban development; sustainable city; city diplomacy